Changes in dynamics of α-chymotrypsin due to covalent inhibitors investigated by elastic incoherent neutron scattering. Issue 37 (12th September 2017) - Andersson, C. D.; Martinez, N.; Zeller, D.; Rondahl, S. H.; Koza, M. M.; Frick, B.; Ekström, F.; Peters, J.; Linusson, A.
Abstract : The dynamics of chymotrypsin increases when bound to two different covalent inhibitors. These effects were analyzed by univariate and multivariate methods. Abstract : An essential role of enzymes is to catalyze various chemical reactions in the human body and inhibition of the enzymatic activity by small molecules is the mechanism of action of many drugs or tool compounds used to study biological processes. Here, we investigate the effect on the dynamics of the serine protease α-chymotrypsin when in complex with two different covalently bound inhibitors using elastic incoherent neutron scattering. The results show that the inhibited enzyme displays enhanced dynamics compared to the free form. The difference was prominent at higher temperatures (240–310 K) and the type of motions that differ include both small amplitude motions, such as hydrogen atom rotations around a methyl group, and large amplitude motions, such as amino acid side chain movements. The measurements were analyzed with multivariate methods in addition to the standard univariate methods, allowing for a more in-depth analysis of the types of motions that differ between the two forms. The binding strength of an inhibitor is linked to the changes in dynamics occurring during the inhibitor-enzyme binding event and thus these results may aid in the deconvolution of this fundamental event and in the design of new inhibitors.